2005
DOI: 10.1128/mcb.25.5.2060-2071.2005
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Poly(A)-Binding Protein Stimulates Translation in Germ Cells

Abstract: The function of poly(A)-binding protein 1 (PABP1) in poly(A)-mediated translation has been extensively characterized. Recently, Xenopus laevis oocytes and early embryos were shown to contain a novel poly(A)-binding protein, ePABP, which has not been described in other organisms. ePABP was identified as a protein that binds AU-rich sequences and prevents shortening of poly(A) tails. Here, we show that ePABP is also expressed in X. laevis testis, suggesting a more general role for ePABP in gametogenesis. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 62 publications
1
89
0
1
Order By: Relevance
“…Since the modulation of translation of the RINGO/Spy mRNA through the PBE operates in the absence of CPEB, ePABP appears to be involved in a novel cytoplasmic polyadenylation-independent process. Previous data with a tethering system indicated that DAZL or ePABP itself is sufficient to promote translation of a reporter in Xenopus oocytes (Collier et al 2005;Wilkie et al 2005). Here it may be significant that ePABP was originally identified not as a PABP but through its direct interaction with an AU-rich upstream sequence in the 3Ј-UTR (Voeltz et al 2001).…”
Section: Translation Regulatory Cascades Genes and Development 141mentioning
confidence: 92%
See 2 more Smart Citations
“…Since the modulation of translation of the RINGO/Spy mRNA through the PBE operates in the absence of CPEB, ePABP appears to be involved in a novel cytoplasmic polyadenylation-independent process. Previous data with a tethering system indicated that DAZL or ePABP itself is sufficient to promote translation of a reporter in Xenopus oocytes (Collier et al 2005;Wilkie et al 2005). Here it may be significant that ePABP was originally identified not as a PABP but through its direct interaction with an AU-rich upstream sequence in the 3Ј-UTR (Voeltz et al 2001).…”
Section: Translation Regulatory Cascades Genes and Development 141mentioning
confidence: 92%
“…Tethering ePABP and also cytoplasmic PABP to a reporter stimulated translation in immature oocytes by eightfold (Wilkie et al 2005), suggesting that both proteins can up-regulate translation. It is also possible that an additional factor contributes to ePABPmediated translation or that ePABP undergoes modification upon meiotic activation and subsequent maturation.…”
Section: Translation Regulatory Cascades Genes and Development 141mentioning
confidence: 99%
See 1 more Smart Citation
“…When their translation is required during late stages of spermatogenesis, the long poly(A)-tails of target mRNAs are shortened to approximately 30 nucleotides to trigger their association with ribosomes for translation [14,16]. In vertebrates, the post-transcriptional or translational control of these mRNAs in germ cells and early embryos are mainly performed by cognate poly(A)-binding proteins, EPAB [17][18][19][20], PABPC1 [20][21][22][23], and PABPC3 [21,22,24] via binding their poly(A) tails.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mRNAs that undergo late polyadenylation often have a CPE overlapping with the poly(A) signal that facilitate the interaction of CPEB with the other factors and the recognition of the CPE, avoiding CPEB phosphorylation and degradation and allowing polyadenylation at later another protein kinase that phosphorylates CPEB. 76,77 The translation of pre-existing maternal mRNAs occurs in a strict temporal order during meiotic cell cycle progression in Xenopus oocytes. 23 Cell cycle dependent signals that regulate the timing of cytoplasmic deadenylation are present in the 3'UTR.…”
Section: Cytoplasmic Polyadenylation/ Deadenylationmentioning
confidence: 99%